The independent predictive value of admission serum ferritin concentration for prognosis in elderly patients with community-acquired pneumonia in the emergency department - Zhang, Xiangqun; Shang, Na; Zhang, Da; Wu, Junyuan; Guo, Shubin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCommunity-acquired pneumonia (CAP) poses a significant health threat to the elderly population, leading to high morbidity and mortality rates. Serum ferritin, a critical indicator of iron metabolism, plays a pivotal role in inflammation and immune regulation. Nevertheless, its specific prognostic relevance in elderly patients with CAP remains unclear. This study aimed to evaluate the predictive capacity of serum ferritin in determining the prognosis of elderly patients with CAP and to investigate its effectiveness when combined with the sequential organ failure assessment (SOFA) or CURB-65 (confusion, uremia, respiratory rate, blood pressure, aged ≥65 years) scores.MethodsThis retrospective cohort study included 451 elderly patients (aged ≥65 years) diagnosed with CAP according to established criteria. Serum ferritin concentrations were measured upon admission and various prognostic indicators such as 28-day mortality, mechanical ventilation requirement, and vasopressor administration were analyzed in conjunction with white blood count (WBC), C-reactive protein (CRP), procalcitonin (PCT), lactate (Lac), SOFA scores, and CURB-65 scores. The independent predictive value of ferritin was assessed through receiver operating characteristic (ROC) curve analysis and multivariate logistic regression.ResultsAmong the 451 patients, 99 (22%) died within 28 days. The area under the curve (AUC) of serum ferritin for predicting 28-day mortality was 0.75 (95%CI: 0.695-0.805). Ferritin outperformed WBC, CRP, and PCT in predictive performance, and its performance was comparable to Lac. When combined with SOFA or CURB-65 scores, the AUC of ferritin for predicting 28-day mortality increased to 0.84 and 0.847, respectively (P<0.001). Moreover, the AUC of ferritin for predicting vasopressor administration was 0.707, which increased to 0.864 and 0.822 when combined with SOFA or CURB-65 scores, respectively (P<0.001). Ferritin could predict mechanical ventilation requirement with an AUC of 0.618, but it was not an independent risk factor, and its predictive ability was not significantly different from other indicators.ConclusionAdmission serum ferritin is an independent predictor for the prognosis of elderly patients with CAP, and it exhibits a strong ability to predict the 28-day mortality and vasopressor administration. The combination of ferritin with SOFA and CURB-65 scores significantly improves the prognostic predictive potency.